Majas Gaya Bahasa pada Lirik Lagu “Asmalibrasi”: Analisis Gaya Bahasa dan Stilistika (International Forum of Researchers and Lecturers, 2023)
The purpose of making this journal is to find out the meaning of the lyrics of the song